2018
DOI: 10.3390/cli6030056
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Building Facades on Outdoor Microclimate—Reflectance Recovery from Terrestrial Multispectral Images Using a Robust Empirical Line Method

Abstract: Climate change and the urban heat island effect pose significant health, energy and economic risks. Urban heat mitigation research promotes the use of reflective surfaces to counteract the negative effects of extreme heat. Surface reflectance is a key parameter for understanding, modeling and modifying the urban surface energy balance to cool cities and improve outdoor thermal comfort. The majority of urban surface studies address the impacts of horizontal surface properties at the material and precinct scales… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 136 publications
(289 reference statements)
0
5
0
Order By: Relevance
“…TARP, Simple Natural Convection, and Ceiling Diffuser were developed for internal SHTCs. The TARP model considers the wind speed and surface roughness, as well as the differences between natural and forced convection, the direction of heat flux, and wind along the building surface [18,32,33]. The researchers have shown that the predictions of BLAST are very close to the actual measurements [34,35].…”
Section: Simulation Processmentioning
confidence: 99%
“…TARP, Simple Natural Convection, and Ceiling Diffuser were developed for internal SHTCs. The TARP model considers the wind speed and surface roughness, as well as the differences between natural and forced convection, the direction of heat flux, and wind along the building surface [18,32,33]. The researchers have shown that the predictions of BLAST are very close to the actual measurements [34,35].…”
Section: Simulation Processmentioning
confidence: 99%
“…While most studies focus on roofs, a lack of data exists for vertical walls and facades, which play a crucial role in the heat exchange between fabrics and ambient air under the canopy. A novel application of the empirical line method to calibrate a terrestrial low-cost multispectral sensor to recover spectral reflectance is developed in Reference [24]; promising results are achieved for this technique, able to characterize the building facades on site. The impact of buildings on energy uses is well recognized worldwide, an optimized procedure for cost optima renovation is carried out in Reference [25].…”
Section: The Interaction Between Buildings and The Urban Environmentmentioning
confidence: 99%
“…In the past, energy performance analyses of urban environments involved comparing urban forms with quantitative measures such as total energy consumption or carbon dioxide emission, but recent studies have chosen to focus on specific aspects of the urban energy system such as buildings or transportation for such analyses. Although macro approaches are convenient and straightforward, they are more challenging to use in practice because of the complexity of the urban energy system (Fox, Osmond, & Peters, 2018;Kasmaee & Tinti, 2018;Kaza, 2010).…”
Section: Introductionmentioning
confidence: 99%